2012
DOI: 10.2967/jnumed.112.104109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Segmentation-Based Attenuation Correction Methods for PET/MRI: Evaluation of Bone and Liver Standardized Uptake Value with Oncologic PET/CT Data

Abstract: For attenuation correction (AC) in PET/MRI systems, segmentation-based methods are most often used. However, the standardized uptake value (SUV) of lesions in the bone and liver, which have higher attenuation coefficients than other organs, can be underestimated, potentially leading to misinterpretation of clinical cases. Errors in SUV estimation are also dependent on the segmentation schemes used in the segmentation-based AC. In this study, this potential bias in SUV estimation using 4 different segmentation-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 26 publications
3
57
2
Order By: Relevance
“…Many factors influence SUV quantification, and among them attenuation correction may play a major role in PET/MRI. It has recently been reported that increasing the numbers of tissue classes used to produce attenuation maps substantially reduces the relative error in measuring SUV leading to a significant decrease in underestimation of SUV by PET/MRI in both lesions and normal tissue [98,99]. Further studies are needed to address these issues, and even more importantly, to assess the reproducibility of quantitative data obtained with PET/MRI.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Many factors influence SUV quantification, and among them attenuation correction may play a major role in PET/MRI. It has recently been reported that increasing the numbers of tissue classes used to produce attenuation maps substantially reduces the relative error in measuring SUV leading to a significant decrease in underestimation of SUV by PET/MRI in both lesions and normal tissue [98,99]. Further studies are needed to address these issues, and even more importantly, to assess the reproducibility of quantitative data obtained with PET/MRI.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…128 As such, different LACs have been assigned to lung tissue class, ranging from 0.018 to 0.035 cm −1 . 26,129 It has been reported that the assignment of a LAC of 0.024 cm −1 to the lungs produces relative errors of 13.5% ± 10.7% (Ref. 34) and 7.7% ± 3.0%.…”
Section: D1 Lungsmentioning
confidence: 99%
“…Another option is to separate both the MRI and PET gantries, at the cost of a longer time examination, one of the gantries remaining unused. In addition, further research is required to maintain a high quality for attenuation correction (50), in order to maintain the semi-quantitative information of PET. the fortuitous discovery of another primary.…”
Section: Future: Petmri?mentioning
confidence: 99%